Post weld heat treatment for high strength steel welded connections. (July 2016) - Zhao, M.S.; Chiew, S.P.; Lee, C.K.
Abstract: In this study, experiments were conducted to investigate the effect of post-weld heat treatment (PWHT) on the reheated, quenched and tempered (RQT) grade S690 high strength steel welded connections. Firstly, the effect of PWHT on the mechanical properties after welding is investigated. It is found that the loss of both strength and ductility after welding could be serious but PWHT could be able to improve the ductility of the affected specimens at the expense of strength. Secondly, four Y-shape plate-to-plate (Y-PtP) and nine T-stub RQT-S690 joints are fabricated to study the effect of PWHT on the residual stress level near the weld toe and the tensile behavior of the joints, respectively. The hole drilling tests employed to study the residual stress reveal that PWHT is able to decrease the residual stress level near the weld toe significantly. The tensile test results show that proper PWHT could improve both the ductility and the maximum resistance while the reduction of plastic resistance can be kept in a negligible level. However, it is found that if the specimens are overheated, although the ductility could still be increased, the reduction of load carrying capacity was severe. Highlights: Effect of PWHT for RQT-S690 welded connections is investigated. PWHT may improve the ductility at the expense of strength. PWHT decreases the residual stress level near the weld toe significantly. Over treatment jeopardize the load carrying capacity.